Evaluation of prefabricated construction systems and materials' thermal performance with reference to housing construction in Saudi Arabia - Alkelani, Abdulaziz (2025)
In light of recent revisions to international standards, such as those advocated by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE), the prioritisation of improved air circulation to support more energy-efficient ventilation systems has become evident. These systems simultaneously enhance occupant satisfaction and thermal comfort. Within this framework, the current research systematically examines the thermal performance and comfort of prefabricated houses in Saudi Arabia, a subject of increasing importance given the rise in summertime temperatures, consistent with the global increase in temperatures.